Experience and adaptability of menstrual cup as a menstrual hygiene management method among its users in Kerala - C., Sreedevi; A. K., Jayasree; Zachariah, Shilu Mariam; N., Divyamol; K. S., Deepak (International Journal Of Community Medicine And Public Health, 2022)
Background: Inadequate menstrual management has long been a major health issue. A growing number of women are turning to menstrual cups as a viable and secure choice. Because it is not an absorbent like tampons, the risk of infection and other severe health problems is rare or absent. Current study is conducted to assess the perceived benefits and difficulties faced by those who use menstrual cup as a method of menstrual hygiene management (MHM) technique. Methods: A cross sectional study was undertaken among 211 women who had used menstrual cup for at least six consecutive cycles. Participants were selected using snowball sampling and data was collected by an online questionnaire. Results: Mean age of participants was 32.16 years and majority got information regarding cup from friends or online sources. Experience of insertion and removal became significantly easier after the third time use onwards. Majority of the health problems and economic difficulty for purchasing MHM products significantly got reduced after starting the use of cup. Few reported allergy and irritation 6 (3%), rashes 2 (1%), dryness 5 (2.5%) and infection 4 (2%). Difficulty in availability of clean water 15 (7.2%), access to clean toilet 3 (1.4%), need for privacy 8 (3.8%) and difficulty in sterilization while travelling 44 (21.2%) were other reported challenges. Improvement in attendance 78 (38.4%), work participation 115 (55.8%), economic benefit 190 (91.3%), health benefits 143 (70.4%) and social activity158 (76.7%) were reported by participants after starting cup use. Conclusions: Menstrual cup is a safe and comfortable alternative. Health concerns are significantly less compared to other MHM products. More awareness campaigns and better availability of cup should be there in the community.